Irrigation systems : design, planning and construction - Laycock, Adrian (CABI, 2007)
Drawing on almost 40 years of experience of irrigation in the developing world, the author introduces fresh ideas on the design of irrigation systems and combines important issues from the disciplines of social conflict, management, and political thinking